Role of hazelnut skin supplementation on plasma antioxidant status and cytokine profile in growing lambs - Ciliberti, Maria Giovanna; Santillo, Antonella; Caroprese, Mariangela; della Malva, Antonella; Natalello, Antonio; Bertino, Antonino; Albenzio, Marzia; Sevi, Agostino (Frontiers in Veterinary Science, 2024)
In this study, the effect of hazelnut skin dietary supplementation on antioxidant status and cytokines profile was evaluated in growing lambs. Twenty-two male lambs at the age of 2 months, balanced for their initial live weight (15.33 ± SD 1.79 kg), were selected and allocated into two experimental groups; the Control group (CON) receiving a maize-barley-based concentrated diet, and the Hazelnut group (HS) receiving supplementation with hazelnut skin (150 g/kg on the dry matter) as maize replacer of the concentrate diet. The experiment lasted for 56 days. Peripheral blood was collected at 7, 35, and 56 days of the experiment. The free radical scavenging activity using 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay, the total antioxidant capacity assay (TAC), and the reactive oxygen species (ROS) and reactive nitrogen species (RNS) were determined in plasma. The secretion of IL-1β, IL-6, and IL-10 cytokines was also determined by ELISA. The DPPH was affected by the interaction between feeding strategy and time of sampling (P=0.039) with a higher level of DPPH at 7 days in HS group than CON group. Time of sampling affected the levels of plasma TAC (P=0.016), while the ROS/RNS levels showed higher value in HS group (P<0.001), on average. The antioxidant/oxidant index, which combines the TAC and the ROS/RNS levels, was not affected by the inclusion of hazelnut skin to the diet (P=0.394). The cytokines' profile showed a lower IL-6 secretion at both 35 and 56 days than at 7 days, on average. Furthermore, the feeding treatment affected the IL-1β level, showing lower level in HS group than in CON one, on average. Lambs from HS group had higher IL-10 plasma levels than CON group at 7 days of the experiment. Present data highlighted an antioxidant effect and a modulatory role in the cytokines' profile of HS in growing lambs.